An ex situ approach to fabricating nanosilica reinforced polyacrylamide grafted guar gum nanocomposites as an efficient biomaterial for transdermal drug delivery application. (4th August 2017) - Dutta, Koushik; Das, Beauty; Mondal, Dipankar; Adhikari, Arpita; Rana, Dipak; Kumar Chattopadhyay, Atis; Banerjee, Rajdeb; Mishra, Roshnara; Chattopadhyay, Dipankar
Abstract : A novel biocompatible TDDS based on nano-silica reinforced polyacrylamide grafted guar-gum nanocomposite. Abstract : Recently transdermal drug delivery systems (TDDS) based on polymeric nanocomposites have been widely researched by polymer and biomedical scientists for the remedy of various diseases. Thus to develop an efficient patch, we have synthesized guar gum- g -polyacrylamide by free radical polymerization using potassium persulphate as an initiator. The transdermal membranes were fabricated via solution casting, by incorporating different wt% of nanosilica and diltiazem hydrochloride to the synthesized copolymer. The resulting copolymer and the nanocomposite membranes were characterized using solid state 13 C nuclear magnetic resonance, Fourier transform infrared spectra, thermo-gravimetric analysis, electron microscopy and viscometry. A hydro-swelling study and surface contact angle measurement showed that the membrane containing 1 wt% nanosilica was the most hydrophobic. The in vitro drug release patterns of all the transdermal membranes showed that the nanocomposite containing 1 wt% nanosilica provides the best result with 8.58 and 24.76% drug release after 5 and 20 h, respectively. Furthermore, the nanocomposite formulation exhibited good cyto-compatibility and non-irritant behaviour, which are primary requirements for an efficient transdermal drug delivery system.